Pemberdayaan Masyarakat dan Intervensi Kesehatan Lingkungan terhadap Penanggulangan Stunting dan Penyakit Menular - Banawestri, Kadek; Widyasari, Ida Ayu Putri Genta (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
This study aims to evaluate the effectiveness of community empowerment and environmental health interventions in overcoming stunting and infectious diseases. The method used was analysis of epidemiological data obtained from UPT Puskesmas Tembuku I, as well as interviews with the community regarding knowledge and health behavior. The results showed that although many communities have high knowledge about nutrition and hygiene, there is a gap between knowledge and daily practice. Educational programs on nutritious diets, sanitation, and environmental hygiene, as well as empowerment of women and health cadres, were shown to increase community awareness. However, the main challenge is behavior change, which requires a more intensive approach and continuous support from various parties. Collaboration between Puskesmas, village governments, and communities is needed to achieve long-term goals in stunting and infectious disease prevention.